A Semantic Analysis of Literal and Figurative Meaning in the Song “Let Her Go” by Passenger - Mita Syah Putri Silalahi; Bernieke Anggita Ristia Damanik (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study examines the construction of literal and figurative meanings in Passenger’s song Let Her Go through a non-empirical qualitative semantic analysis based on textual interpretation. The primary data consist of the official lyrics of the song, analyzed through close reading, semantic categorization, and contextual interpretation informed by semantic and discourse theories. The findings indicate that literal meanings function as experiential grounding that represents emotional states such as loneliness and introspection in a direct and descriptive manner. Figurative meanings, however, dominate the lyrical structure through metaphors, symbolism, contrast, and paradox that articulate complex emotional themes of love, loss, regret, and delayed realization. In addition, the recurrent structural pattern “only know… when…” strengthens thematic coherence by emphasizing retrospective awareness as the central message of the song. The interaction between literal and figurative meanings constructs a layered semantic system in which emotional depth emerges from the interplay between denotative description and connotative representation. These findings confirm that meaning in song lyrics is dynamically constructed through contextual and interpretative processes.